2023
DOI: 10.1097/cm9.0000000000002525
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immune microenvironment-modulated nanostrategy for the treatment of lung cancer metastasis

Abstract: As one of the most malignant tumors worldwide, lung cancer, fueled by metastasis, has shown rising mortality rates. However, effective clinical strategies aimed at preventing metastasis are lacking owing to its dynamic multi-step, complicated, and progressive nature. Immunotherapy has shown promise in treating cancer metastasis by reversing the immunosuppressive network of the tumor microenvironment. However, drug resistance inevitably develops due to inadequate delivery of immunostimulants and an uncontrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
0
0
0
Order By: Relevance
“… 52 , 53 Metastasis involves a series of complex processes, including the shedding of tumor cells, degradation of extracellular matrix (ECM), invasion, migration, and adhesion of endothelial cells, as well as the reconstruction and growth at a distance, which require the interaction of different signaling pathways. 54 Astragalus membranaceus has attracted widespread attention in TCM treating NSCLC due to its synergistic effect and minimal side effects. Early studies have shown that Astragalus membranaceus can inhibit the invasion and metastasis of tumor cells.…”
Section: Pharmacological Activity Of Astragalus Membranaceus In Nsclcmentioning
confidence: 99%
“… 52 , 53 Metastasis involves a series of complex processes, including the shedding of tumor cells, degradation of extracellular matrix (ECM), invasion, migration, and adhesion of endothelial cells, as well as the reconstruction and growth at a distance, which require the interaction of different signaling pathways. 54 Astragalus membranaceus has attracted widespread attention in TCM treating NSCLC due to its synergistic effect and minimal side effects. Early studies have shown that Astragalus membranaceus can inhibit the invasion and metastasis of tumor cells.…”
Section: Pharmacological Activity Of Astragalus Membranaceus In Nsclcmentioning
confidence: 99%